Bibliometric Analysis of Sharia Finance Research from a Global Perspective for the Period 2010–2024 - Loso Judijanto (West Science Journal Economic and Entrepreneurship, 2026)
This study aims to examine the development and structure of global research on Sharia finance through a bibliometric analysis of publications indexed in the Scopus database from 2010 to 2024. Using bibliometric techniques and visualization tools such as VOSviewer, this study analyzes publication trends, collaboration networks among authors, institutions, and countries, as well as the thematic evolution of research topics in the field of Islamic finance. The results indicate that research on Sharia finance has grown significantly during the observed period, reflecting the increasing global importance of Islamic financial systems. The collaboration analysis shows that several key authors and institutions play central roles in connecting different research groups, while countries such as Indonesia, Malaysia, Saudi Arabia, the United Kingdom, and the United States emerge as important contributors to the global research network. Keyword co-occurrence analysis reveals that dominant themes include Islamic banking, Sharia compliance, financial institutions, and Islamic law. At the same time, emerging topics such as financial technology (fintech), blockchain, decentralized finance, and financial inclusion indicate a shift toward digital transformation and innovation in Islamic financial services. Furthermore, themes related to sustainable development, ESG, and waqf highlight the growing integration of Islamic finance with broader sustainability and ethical finance agendas. This study provides a comprehensive overview of the intellectual structure, collaboration patterns, and emerging research trends in Sharia finance, offering valuable insights for future academic research and policy development in the global Islamic financial industry.